Long spin lifetimes of charge carriers in rubrene crystals due to fast transient-localization motion - Carey, Remington L.; Ren, Xinglong; Jacobs, Ian E.; Elsner, Jan; Schott, Sam; Goldberg, Elliot; Wang, Zichen; Blumberger, Jochen; Sirringhaus, Henning (Nature communications, 2025)
Field-induced electron spin resonance provides valuable insights into the interplay between spin and charge dynamics in organic semiconductors. We apply this technique to ion-gel-gated capacitors and conventional field-effect transistors to study the temperature-dependent carrier dynamics of high-mobility rubrene single-crystals. Unlike previous measurements on other molecular and polymer semiconductors, we observe remarkably long spin relaxation times—on the order of microseconds—persisting from room temperature down to 15 K. Such long relaxation times are caused by the rapid transient-localization motion of charge carriers, which induces efficient motional narrowing. Additionally, by leveraging the high injection efficiency of ion-gel-gated devices, we observe spin lifetimes shortening at high carrier concentrations. This is attributed to emerging spin-spin dipolar interactions and can be modelled using an approach adapted from fluid-phase nuclear magnetic resonance. Our work demonstrates that field-induced electron spin resonance provides a powerful probe of the transient-localization physics of high-mobility molecular crystals. Spin relaxation in organic semiconductors is normally strongly correlated with temperature, varying over many orders of magnitude from 4 K to 300 K. Here, the authors report stable, microsecond-long spin lifetimes in rubrene single crystals due to the rapid transient localization of charge carriers.